2021
DOI: 10.1002/mabi.202100077
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Composed of PEGylated Alternating Copolymer‐Combretastatin A4 Conjugate for Cancer Therapy

Abstract: Chemotherapy using vascular targeting agents is an emerging new approach for cancer therapy. Combretastatin A4 (CA4) is a leading vascular‐disrupting agent that targets the tumor blood vasculature for clinical tumor elimination. However, the extremely poor water solubility of CA4 hinders its biomedical applications. In this study, nanoparticles composed of novel PEGylated alternating copolymer‐CA4 conjugates are designed to improve the therapeutic efficiency of CA4. First, an alternating copolymer with an alke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The residue was chromatographed on a silica gel column with ethyl acetate and n-hexane as an eluent to yield compound 3-(((4-nitrophenoxy) carbonyl) amino) benzo[e][1,2,4]triazine 1,4-dioxide (TPZ-NPC) as a yellow powder (600.0 mg). 1…”
Section: Synthesis Of Tpz-npcmentioning
confidence: 99%
See 2 more Smart Citations
“…The residue was chromatographed on a silica gel column with ethyl acetate and n-hexane as an eluent to yield compound 3-(((4-nitrophenoxy) carbonyl) amino) benzo[e][1,2,4]triazine 1,4-dioxide (TPZ-NPC) as a yellow powder (600.0 mg). 1…”
Section: Synthesis Of Tpz-npcmentioning
confidence: 99%
“…The residue was chromatographed on a silica gel column with ethyl acetate and n-hexane as an eluent to yield compound 3-(3-(5-hydroxypentyl) ureido)benzo[e][1,2,4]triazine 1,4-dioxide (TPZH) as a red powder (270.5 mg). 1 H NMR (500 MHz, DMSO-d6): δ 9.81 (s, 1H), 8.32-8.25 (m, 4H), 8.06-8.01 (m, 1H), 7.79-7.73 (m, 1H), 7.64-7.60 (t, 1H), 4.42-4.39 (t, 1H), 3.43-3.37 (q, 2H), 3.18-3.11 (q, 2H), 1.52-1.30 (m, 6H…”
Section: Synthesis Of Tpzhmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies confirmed biocompatibility of CA4-NPs against 4T1 cells, and animal studies demonstrated enhanced therapeutic efficacy in 4T1-tumor bearing mice. [65] Sorafenib (SFN) is known to inhibit cancer cell proliferation and angiogenesis as it binds to VEGFR-2, VEGFR-3, and PDGFR-β, and is the only FDA approved medicine for treatment of advanced HCC. However, only 30 % patients respond to SFN, and clinical usage of SFN is limited due to its low response rate, poor water solubility, poor pharmacokinetic profile, and systemic side-effects.…”
Section: Nc[d]) Liposomes Containing Ca4 (L[c]) Combination Of L[c] +...mentioning
confidence: 99%
“…Synthetic polypeptides are one of the most important and irreplaceable biomaterials, because of the advantages of high transport efficiency, low toxicity, no obvious restriction on the size of all substances, no inflammatory response 17–19 . Our group has developed a series of polypeptide‐based copolymers for anticancer drug delivery 20–24 . Specifically, poly( l ‐glutamic acid)‐ graft ‐poly(ethylene glycol) (PLG‐ g ‐PEG) was designed and synthesized for combretastatin A4 (CA4) conjugation.…”
Section: Introductionmentioning
confidence: 99%